The definitions of health care and social welfare informatics competencies - Minna Tiainen; Outi Ahonen; Leena Hinkkanen; Elina Rajalahti; Alpo Värri (Finnish Social and Health Informatics Association, 2021)
Digital transformation is changing the ecosystem and at the same time professionals' competencies worldwide. Minimising health care and social welfare costs while increasing citizens' health and well-being is challenging. Technology and digital tools play an important role in reaching this goal. However, there are inequalities concerning technology, and this has many impacts. Digitalisation brings challenges not only to health care and social welfare professionals but to citizens, too. Working with or using services in digital environments demands new skills. This has social and ethical impacts, e.g. how is equal access to services ensured. Health and social care professionals should have different competencies to respond to this, such as societal competencies. The purpose of this article is to describe how the definition of competencies in health care and social welfare version 1.0 (developed in the national SotePeda 24/7 project) was finalised as the final version 2.0 for Finnish healthcare and social welfare education by experts' evaluation. Data was collected through an electronic questionnaire administered to selected experts (N=140) during January 2020. The number of experts who responded to the study was 52. These experts (social and health, business and IT) work or have worked in tasks related to the digitalisation of social and health care. The questionnaire was based on version 1.0 of the definition of digital competencies of health care and social welfare informatics. The questionnaire was mainly quantitative, but it also included open-ended qualitative questions. The experts agreed to a large extent on the version 1.0 definition, but some adjustments were made to the definition based on our study. The resulting definition is intended for use in the planning, implementation and evaluation of health care and social welfare education, but it can also be used for polytechnic education. The aim is to develop the digital skills of educators, degree students and in-service trainees in a multidisciplinary way (social and health, business and IT) to meet the needs of working life.